'Candidatus Phytoplasma asteris' and 'Candidatus Phytoplasma aurantifolia', New Phytoplasma Species Infecting Apple Trees in Iran. Issue 7 (10th January 2014) - Hashemi‐Tameh, Mahdis; Bahar, Masoud; Zirak, Leila
Abstract During several surveys in extensive areas in central Iran, apple trees showing phytoplasma diseases symptoms were observed. PCR tests using phytoplasma universal primer pairs P1A/P7A followed by R16F2n/R16R2 confirmed the association of phytoplasmas with symptomatic apple trees. Nested PCR using 16SrX group‐specific primer pair R16(X)F1/R1 and aster yellows group‐specific primer pairs rp(I)F1A/rp(I)R1A and fTufAy/rTufAy indicated that apple phytoplasmas in these regions did not belong to the apple proliferation group, whereas aster yellows group‐related phytoplasmas caused disease on some trees. Restriction fragment length polymorphism (RFLP) analyses using four restriction enzymes (HhaI, HpaII, HaeIII and RsaI) and sequence analyses of partial 16S rRNA and rp genes demonstrated that apple phytoplasma isolates in the centre of Iran are related to 'Ca. Phytoplasma asteris' and 'Ca. Phytoplasma aurantifolia'. This is the first report of apples infected with 'Ca. Phytoplasma asteris' in Iran and the first record from association of 'Ca. Phytoplasma aurantifolia' with apples worldwide.